Composite material structure, preparation method thereof and application of composite material structure in lithium battery
By using a hydrophilic polyaryle base layer and a dense hydrophilic composite material layer in the lithium battery separator to form a gradient void structure, the problem of insufficient adsorption capacity of the existing separator material is solved, and the safety and service life of the battery are improved.
Patent Information
- Application Number
- CN202411934241.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The hydrophobicity of existing lithium battery separators leads to insufficient penetration and adsorption capacity of the electrolyte, affecting the safety and service life of the battery.
The hydrophilic polyaryl ester base layer and a dense hydrophilic composite material layer are used to form a gradient void structure through electrospinning technology to improve the adsorption and permeability of the electrolyte.
It enhances the deformation resistance and mechanical properties of the composite material structure, while significantly improving the adsorption and permeability of the electrolyte and extending the service life of the battery.
Smart Images

Figure CN119764756A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery separators, and in particular to a composite material structure and a preparation method thereof and an application in lithium batteries. Background Art
[0002] With the rapid development of electronic products and electric vehicles, the requirements for lithium battery performance are also increasing. The separator of lithium batteries plays a vital role as the physical isolation layer between the positive and negative electrodes in the battery. It must not only have good electrical insulation, but also have certain mechanical strength, thermal stability and electrolyte adsorption capacity to ensure the safe and reliable operation of the battery during charging and discharging. Among them, polyarylate fiber has good mechanical strength, thermal stability and chemical stability, and can be used as a potential material source for separator paper.
[0003] In the related art, there are a large number of ester groups on the molecular chain of polyarylate, which is hydrophobic in itself and easily forms lipophilic areas on its surface, limiting the penetration and adsorption capacity of the electrolyte. If polyarylate fibers and fiber materials with strong wettability are mixed to make diaphragm paper, although the wettability and electrochemical properties of diaphragm paper can be improved, the strength and thermal stability of diaphragm paper will be significantly reduced, making the diaphragm easy to be punctured and burned, affecting the service life of diaphragm paper. Summary of the invention
[0004] In view of the above problems, the present application is proposed. The present application provides a composite material structure and a preparation method thereof and an application in a lithium battery.
[0005] According to one aspect of the present application, there is provided a composite material structure, comprising:
[0006] A hydrophilic polyarylate base layer and a hydrophilic composite material layer arranged on the hydrophilic polyarylate base layer, wherein the pore size of the hydrophilic composite material layer is smaller than the pore size of the hydrophilic polyarylate base layer.
[0007] According to another aspect of the present application, a method for preparing a composite material structure is provided, comprising:
[0008] Step 1: disintegrating polyarylate short fibers and polyarylate pulp fibers into slurry in water, and making slurry, and obtaining a polyarylate base layer after drying;
[0009] Step 2: dissolving and dispersing polyarylate powder, fluorine-containing resin, nano zirconium dioxide and nano cellulose in a mixed solvent to obtain a spinning solution;
[0010] Step 3: electrospinning the polyarylate substrate layer using a spinning solution to form a composite material layer, thereby obtaining a composite material structure intermediate;
[0011] Step 4: Perform hydrophilic treatment on the composite material structure intermediate to obtain the composite material structure.
[0012] In one or more technical solutions provided in the embodiments of the present disclosure, the pore size of the hydrophilic composite material layer is smaller than the pore size of the hydrophilic polyarylate substrate layer. Therefore, compared with the hydrophilic polyarylate substrate layer, the structure of the hydrophilic composite material layer is more compact. When an external force acts on the composite material structure, the compact hydrophilic composite material layer can effectively disperse stress and bear more loads, thereby improving the anti-deformation ability of the composite material structure, making it difficult to be pierced during use. On this basis, the polyarylate substrate layer and the composite material layer in the embodiment of the present application are both hydrophilic in nature, so when it is contacted with the electrolyte, the adsorption and penetration capacity of the electrolyte can be significantly increased. In addition, the hydrophilic polyarylate substrate layer enables the composite material structure to maintain excellent mechanical properties and thermal stability due to the presence of polyarylate. At the same time, due to the large pore size of the hydrophilic polyarylate substrate layer and the small pore size of the hydrophilic composite material layer, a gradient gap from large to small is formed between the hydrophilic polyarylate substrate layer and the hydrophilic composite material layer. This gradient gap is like a gradually tapering channel network, which provides favorable conditions for the adsorption and penetration of the electrolyte. This gradient void increases the specific surface area of the material, and when the composite material structure comes into contact with the electrolyte, it can provide more adsorption sites, thereby further increasing the composite material structure's adsorption capacity for the electrolyte. According to the principle of capillary phenomenon, when a liquid comes into contact with a solid with fine pores, if the liquid can wet the solid surface, the liquid will rise in the pores. In this gradient void, the larger pores of the hydrophilic polyarylate substrate layer are like a "reservoir" that can quickly absorb the electrolyte, while the smaller pores of the hydrophilic composite material layer further adsorb the electrolyte into the material through capillary action. Not only that, this gradient void can serve as a channel to guide the electrolyte adsorbed in the material through the composite material structure along the channel, thereby further increasing the composite material structure's ability to penetrate the electrolyte.
[0013] According to another aspect of the present application, there is provided a use of a slurry prepared by the above composite material structure and / or the preparation method of the above composite material structure in a lithium battery.
[0014] Compared with the prior art, the beneficial effects of the composite material structure provided in the present application and / or the composite material structure prepared by the preparation method of the above-mentioned composite material structure in the application of lithium batteries are the same as the beneficial effects of the above-mentioned composite material structure and its preparation method, which will not be repeated here.
[0015] It is to be understood that both the foregoing general description and the following detailed description are exemplary, and are intended to provide further explanation of the technology as claimed. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] By describing the embodiments of the present application in more detail in conjunction with the accompanying drawings, the above and other purposes, features and advantages of the present application will become more apparent. The accompanying drawings are used to provide a further understanding of the embodiments of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the present application and do not constitute a limitation of the present application. In the accompanying drawings, the same reference numerals generally represent the same components or steps.
[0017] Figure 1 A schematic structural diagram of a composite material structure according to an embodiment of the present application is shown;
[0018] Figure 2 A flow chart showing a method for preparing a composite material structure according to an embodiment of the present application is shown. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present application more obvious, the exemplary embodiments according to the present application will be described in detail with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application, and it should be understood that the present application is not limited to the exemplary embodiments described here.
[0020] With the rapid development of electronic products and electric vehicles, the requirements for lithium battery performance are also constantly increasing, especially in terms of safety, energy density and service life. The separator of lithium batteries plays a vital role as a physical isolation layer between the positive and negative electrodes in the battery. It not only needs to have good electrical insulation, but also needs to have certain mechanical strength, thermal stability and electrolyte adsorption capacity to ensure the safe and reliable operation of the battery during charging and discharging. Traditional lithium battery separator materials mainly include polyolefin compounds and some high molecular polymers, but this material has strong hydrophobicity and usually has poor electrolyte adsorption capacity, which may cause electrolyte leakage or battery performance degradation under high load or high temperature. In addition, this material is prone to deformation or rupture under extreme conditions such as high pressure and high temperature, thus affecting the stability and safety of the battery. Not only that, this material has poor thermal stability, and the separator paper made of this material is prone to heat shrinkage, melting or degradation under high temperature environment, which has an adverse effect on the operation of the battery. In recent years, polyarylate fiber has begun to attract the attention of researchers as a new material. Polyarylate fiber has good mechanical strength, thermal stability and chemical stability and can be used as a potential material source for separator paper.
[0021] In the related art, there are a large number of ester groups on the molecular chain of polyarylate, which is hydrophobic in itself and easily forms lipophilic areas on its surface, limiting the penetration and adsorption capacity of the electrolyte. If polyarylate fibers and fiber materials with strong wettability (such as cellulose) are mixed to make diaphragm paper, although the wettability and electrochemical properties of the diaphragm paper can be improved, the strength and thermal stability of the diaphragm paper will be significantly reduced, making the diaphragm easy to be punctured and burned, affecting the service life of the diaphragm paper.
[0022] In view of the above problems, the present application provides a composite material structure that can improve the adsorption and penetration capacity of electrolyte while maintaining the excellent mechanical properties and thermal stability of polyarylate fibers. Figure 1 The schematic diagram of the structure of the composite material structure of the embodiment of the present application is shown. Figure 1 As shown, the composite material structure includes: a hydrophilic polyarylate base layer 1 and a hydrophilic composite material layer 2 arranged on the hydrophilic polyarylate base layer 1 , wherein the pore size of the hydrophilic composite material layer 2 is smaller than the pore size of the hydrophilic polyarylate base layer 1 .
[0023] It is understandable that the pore size of the hydrophilic composite material layer 2 in the embodiment of the present application is smaller than the pore size of the hydrophilic polyarylate base layer 1, therefore, compared with the hydrophilic polyarylate base layer 1, the structure of the hydrophilic composite material layer 2 is more compact, and when external force acts on the composite material structure, the compact hydrophilic composite material layer 2 can effectively disperse stress and bear more loads, thereby improving the anti-deformation ability of the composite material structure, making it difficult to be pierced during use. On this basis, the polyarylate base layer and the composite material layer in the embodiment of the present application are hydrophilic properties, therefore, when it is contacted with the electrolyte, the adsorption and penetration capacity of the electrolyte can be significantly increased. In addition, the hydrophilic polyarylate base layer 1 is due to the presence of polyarylate, so that the composite material structure can maintain excellent mechanical properties and thermal stability. At the same time, due to the large pore size of the hydrophilic polyarylate base layer 1 and the small pore size of the hydrophilic composite material layer 2, a gradient gap from large to small is formed between the hydrophilic polyarylate base layer 1 and the hydrophilic composite material layer 2. This gradient void is like a network of gradually tapering channels, providing favorable conditions for the adsorption and penetration of electrolytes. This gradient void increases the specific surface area of the material, and when the composite material structure is in contact with the electrolyte, it can provide more adsorption sites, thereby further increasing the adsorption capacity of the composite material structure for the electrolyte. According to the principle of capillary phenomenon, when a liquid contacts a solid with fine pores, if the liquid can wet the solid surface, the liquid will rise in the pores. In this gradient void, the larger pores of the hydrophilic polyarylate substrate layer 1 are like a "reservoir" that can quickly absorb the electrolyte, while the smaller pores of the hydrophilic composite material layer 2 further adsorb the electrolyte into the material through capillary action. Not only that, this gradient void can serve as a channel to guide the electrolyte adsorbed in the material through the composite material structure along the channel, thereby further increasing the penetration capacity of the composite material structure for the electrolyte.
[0024] In an optional manner, the porosity of the hydrophilic composite material layer in the embodiment of the present application is 0.25 to 1.2 times the porosity of the hydrophilic polyarylate base layer, and the pore size of the hydrophilic composite material layer is 0.033 to 0.6 times the pore size of the polyarylate base layer.
[0025] Exemplarily, the porosity of the hydrophilic polyarylate substrate layer in the embodiment of the present application is 50% to 80%, the pore size of the hydrophilic polyarylate substrate layer is 0.5μm to 3μm, the porosity of the hydrophilic composite material layer is 20% to 60%, and the pore size of the hydrophilic composite material layer is 0.1μm to 0.3μm. It can be seen that the pore size of the hydrophilic composite material layer is smaller than the pore size of the hydrophilic polyarylate substrate layer. Therefore, compared with the hydrophilic polyarylate substrate layer, the structure of the hydrophilic composite material layer is more compact, which is beneficial to improve the mechanical strength of the composite material structure and extend its service life. In addition, the above-mentioned obvious pore size difference constitutes the gradient pores of the composite material structure in the embodiment of the present application, which is beneficial to improve the adsorption and penetration capacity of the electrolyte on the basis of ensuring the excellent mechanical properties and thermal stability of the polyarylate fiber.
[0026] In an optional manner, the material of the hydrophilic polyarylate base layer in the embodiment of the present application includes polyarylate staple fibers and polyarylate pulp fibers. The polyarylate staple fibers can increase the mechanical strength of the hydrophilic polyarylate base layer, and the polyarylate pulp fibers can fill the gaps between the polyarylate staple fibers, so that the fibers in the structure of the base layer are more evenly distributed, and the probability of excessive aggregation of the polyarylate staple fibers is reduced, thereby ensuring the performance stability of the base layer.
[0027] On this basis, the embodiment of the present application defines the length of the polyarylate staple fiber as 5mm to 20mm. Compared with the polyarylate pulp fiber, the length of the polyarylate staple fiber is longer. When the various polyarylate staple fibers are interwoven together, the overall strength of the hydrophilic polyarylate base layer can be significantly increased, and the probability of the composite material structure being broken by impact is reduced. At the same time, the embodiment of the present application also defines the fineness of the polyarylate staple fiber as 1.1D to 3.3D. At this time, the purpose of controlling the porosity of the hydrophilic polyarylate base layer can be achieved by controlling the fineness of the polyarylate staple fiber. In addition, the embodiment of the present application also defines the length of the polyarylate pulp fiber as 1mm to 2.5mm. At this time, its relatively short length and special pulp morphology make it have a larger specific surface area in the base layer. This larger specific surface area can adsorb more water molecules, thereby improving the hydrophilicity of the base layer.
[0028] For example, the weight percentage of the hydrophilic polyarylate base layer is 20 to 70 parts, and the weight percentage of the polyarylate pulp fiber is 35 to 80 parts. 2 ~40g / m 2 It can be seen that the hydrophilic polyarylate substrate layer is relatively thin, which is beneficial to improve the electron transmission capacity. When the weight of the hydrophilic polyarylate substrate layer is less than 2g / m 2 , its mechanical strength is low, and it cannot resist external forces in long-term use, which has an adverse effect on its service life; when the quantitative weight of the hydrophilic polyarylate substrate is higher than 40g / m2 , the diffusion distance of lithium ions in the composite material structure increases, resulting in an increase in ion migration resistance, which will reduce the charge and discharge efficiency of the battery. Preferably, when the weight of the hydrophilic polyarylate substrate is 10 g / m 2 ~20g / m 2 When the material is treated with a high-strength quartz crystal, its mechanical strength and ionic conductivity can be guaranteed to be at a good level.
[0029] In an optional manner, the raw materials of the hydrophilic composite material layer in the embodiment of the present application include polyarylate powder and fluororesin. According to the mass fraction in the hydrophilic composite material layer, the polyarylate powder is 30 to 50 parts, and the fluororesin is 50 to 70 parts. Within the above parameter range, the bonding effect of the fluororesin ensures the uniform distribution of the polyarylate powder in the composite material layer, so that the polyarylate powder can give full play to its enhancement function. At the same time, the polyarylate powder provides rigid support for the material. This synergistic effect effectively improves the mechanical strength of the hydrophilic composite material layer, which can better adapt to the mechanical requirements in various application scenarios.
[0030] Illustratively, the fluorine-containing resin in the embodiments of the present application includes one or more of polyvinylidene fluoride and fluorinated ethylene propylene copolymer.
[0031] In an optional manner, the raw materials of the hydrophilic composite material layer in the embodiment of the present application further include nanocellulose, nano zirconium dioxide and a mixed solvent, and according to the mass fraction in the hydrophilic composite material layer, the nanocellulose is 0.05 to 0.2 parts, the nano zirconium dioxide is 10 to 50 parts, and the mixed solvent is 480 to 3922 parts. Among them, the nano zirconium dioxide can enhance the lyophilicity and ionic conductivity of raw materials such as polyarylate powder and fluorine-containing resin.
[0032] Exemplarily, the mixed solvent in the embodiment of the present application includes a halogen salt and a polar solvent of a cationic polar oxygen group complexed with the halogen salt, and the halogen salt is 1 to 10 parts and the polar solvent is 90 to 99 parts according to the mass fraction in the mixed solvent. Within the above parameter range, the halogen salt can dissociate ions in the mixed solvent. These ions can increase the ion concentration of the solution, thereby improving the ionic conductivity of the mixed solvent. In the process of preparing the composite material, the polar solvent can not only dissolve the halogen salt, but also make the polar groups on the surface of the polyarylate powder interact with the solvent molecules, so that the powder is evenly dispersed in the solvent to avoid agglomeration. Specifically, the halogen salt in the embodiment of the present application includes at least one of lithium chloride, potassium chloride, sodium chloride, lithium bromide and sodium bromide, and the polar solvent includes one or more of dimethylacetamide, methyl pyrrolidone and dimethylformamide.
[0033] The embodiment of the present application also provides a method for preparing the above-mentioned composite material structure to prepare a composite material structure with good mechanical properties, thermal stability, and adsorption and penetration capabilities of electrolyte. Figure 2 The flowchart of the method for preparing the composite material structure of the embodiment of the present application is shown. Figure 2 As shown, the steps are as follows:
[0034] Step 1: Disperse the polyarylate staple fibers and polyarylate pulp fibers into slurry in water, and paper-make the slurry, and obtain the polyarylate base layer after drying.
[0035] Exemplarily, the beating degree of the polyarylate staple fiber of the embodiment of the present application is 20°SR~50°SR. When within this parameter range, the bonding area between the fibers can be increased, so that after drying, the internal structure of the polyarylate base layer is more solid, the mechanical strength is improved, and it can better withstand external forces. At the same time, the beating degree is controlled within the above range, and the porosity and pore size of the formed polyarylate base layer can be regulated to prepare a polyarylate base layer that meets expectations. At the same time, the embodiment of the present application also limits the speed of delamination to 1000 rpm~6000 rpm, at which time, the fibers can be evenly dispersed in water to form a slurry. If the speed of delamination is less than 1000 rpm, the production efficiency will be reduced; if the speed of delamination is greater than 6000 rpm, the fibers will be over-cut or the surface properties will be destroyed, thereby adversely affecting the performance of the polyarylate base layer. It should be understood that the delamination time in the embodiment of the present application can be adjusted according to actual conditions, and no adjustment is made here. In addition, the embodiment of the present application also limits the drying temperature to 100°C to 200°C, so that the porosity and pore size of the polyarylate base layer can be further regulated. When the drying temperature is lower than 100°C, the drying efficiency will be lower; when the drying temperature is higher than 200°C, the water evaporation rate will be accelerated. In this process, the fibers and other components in the slurry may quickly approach and squeeze each other due to the rapid loss of water, resulting in a decrease in porosity and a smaller pore size, which is not conducive to ensuring the yield of the polyarylate base layer. In addition, the slurry papermaking device can be adjusted according to actual conditions and is not limited here.
[0036] Step 2: dissolving and dispersing polyarylate powder, fluorine-containing resin, nano zirconium dioxide and nano cellulose in a mixed solvent to obtain a spinning solution.
[0037] Exemplarily, polyarylate powder, nano zirconium dioxide, fluorine-containing resin, and nano cellulose are dissolved and dispersed in a mixed solvent, stirred at 85°C for 1h, with a rotation speed of 1200 rpm, taken out and left to cool, and a spinning solution is obtained after defoaming treatment. Among them, the polar solvent in the mixed solvent can make the solute molecules and halogen ions including polyarylate powder, nano zirconium dioxide, fluorine-containing resin and nano cellulose uniformly dispersed, and under the action of the electric field, the stability of the solution can be guaranteed, so that the subsequent steps (for example, the spinning process) can be carried out smoothly. Similarly, when the polar solvent includes one or more of dimethylacetamide, methyl pyrrolidone and dimethylformamide, its volatility is moderate, which can further ensure that the subsequent steps (for example, the spinning process) can be carried out smoothly. At the same time, nano zirconium dioxide can increase the lyophilicity of the spinning solution and can also improve the ionic conductivity.
[0038] Step 3: electrospinning the polyarylate substrate layer using a spinning solution to form a composite material layer, thereby obtaining a composite material structure intermediate.
[0039] Exemplarily, the spinning solution is injected into the electrospinning device for electrospinning, with the polyarylate substrate layer as the receiving substrate, and the spraying amount is 1 g / m 2 ~20g / m 2 , so that the fibers in the formed composite material layer are more closely interwoven, and the formed network structure is more solid, thereby improving the mechanical properties of the composite material structure intermediate such as tensile resistance and bending resistance. Among them, the pressure of electrospinning is 10kv~40kv, which helps to form more uniform fibers; the distance between the jet needle and the receiving roller is 10cm~50cm. In the process of the solution being sprayed from the needle to the roller, the fiber will continue to be stretched by the electric field force within this distance, making the fiber thinner. At the same time, the longer distance also increases the time for the solvent to evaporate, which is conducive to better drying and curing of the fiber before reaching the receiving roller; the spinning solution propulsion speed is 0.01ml / h~1ml / h, which is conducive to ensuring the stability of the spinning process; the temperature is 30℃~40℃, and within this temperature range, the solvent evaporation rate is moderate. The appropriate temperature can make the solvent gradually evaporate during the fiber stretching process, so that the fiber can be cured in time; the relative humidity is 10%~40%, which is conducive to regulating the solvent evaporation rate and fiber quality. The number of needles in the electrospinning device is 1,000 to 3,000, which can evenly distribute the spinning solution on the surface of the substrate layer to avoid local fiber accumulation or fiber missing areas, so that the structure of the formed composite material layer is more uniform. The receiving device of the electrospinning device is a flat plate collection, on which the polyarylate substrate layer is laid.
[0040] Exemplarily, step three also includes: cleaning and hot pressing the composite material structure intermediate. Among them, the cleaning method is ultrasonic cleaning, the cleaning liquid includes ethanol, and the cleaning time is 1-10min to remove the residual solvent on the surface of the composite material structure intermediate. The temperature of the hot pressing treatment is 240℃~320℃, and the pressure of the hot pressing treatment is 5~10MPa. Within the above parameter range, it is beneficial to improve the interlayer bonding force of the composite material layer, and ensure that its porosity meets 20%~60%, and the pore size meets 0.05μm~0.7μm. It can be understood that the hot pressing method in the embodiment of the present application is roller hot pressing molding, and its speed can be adjusted according to actual conditions, which is not limited here.
[0041] Step 4: Perform hydrophilic treatment on the intermediate of the composite material structure to obtain a composite material structure. The hydrophilic treatment is performed by plasma treatment, the vacuum degree of the hydrophilic treatment is 5Pa to 100Pa, the output power of the hydrophilic treatment is 100W to 500W, and the time of the hydrophilic treatment is 5min to 30min, which can increase the number of polar groups on the surface of the intermediate of the composite material structure to improve the adsorption and penetration capacity of the composite material structure to the electrolyte.
[0042] The present application also provides an application of the composite material structure and / or the composite material structure prepared by the preparation method of the composite material structure in a lithium battery. The application is the application in diaphragm paper. When the composite material structure is made into diaphragm paper, it has good adsorption and penetration ability for electrolyte, improves the current transmission efficiency, and has good mechanical properties, prolonging the service life.
[0043] In order to verify the effect of the composite material structure provided in the examples of the present application, the examples of the present application are demonstrated by way of examples and comparative examples.
[0044] Embodiment 1
[0045] Step 1: According to the mass percentage, 75 parts of polyarylate staple fibers and 25 parts of polyarylate pulp fibers are dissolved in 10,000 parts of water at a speed of 3,100 rpm for 10 minutes to form a slurry, and placed in a slurry tank with a stirring speed of 50 rpm, and then wet-coated through an inclined mesh paper base at a speed of 17 m / min. After the papermaking is formed, it is dried at 125°C to obtain a polyarylate base layer.
[0046] The length of the polyarylate staple fiber is 7 mm, the fineness of the polyarylate staple fiber is 1D, the length of the polyarylate pulp fiber is 2.5 mm, the beating degree is 32°SR, and the basis weight of the polyarylate base layer is 30 g / m 2 .
[0047] Step 2: Dissolve and disperse 30 parts of polyarylate powder, 60 parts of polyvinylidene fluoride, 10 parts of nano zirconium dioxide and 0.1 parts of nano cellulose in 900 parts of a mixed solvent by mass, stir at 80°C for 1 hour, take out and let stand to cool for 15 minutes, and then filter and defoam to obtain a spinning solution.
[0048] The mixed solvent includes 10 parts of lithium chloride and 890 parts of methyl pyrrolidone.
[0049] Step three: inject the spinning solution into the electrospinning equipment, lay a polyarylate base layer on the receiving device, perform electrospinning to form a composite material layer, and obtain a composite material structure intermediate. Then, place the composite material structure intermediate in an ultrasonic cleaning tank for cleaning for 3 minutes. The cleaning liquid is 55% ethanol solution. After cleaning, it is dried at 90°C and rolled and hot-pressed.
[0050] Among them, the amount of spinning solution is 10g / m 2 The pressure of the electrospinning equipment is 25kv, the distance between the jet needle and the receiving roller is 30cm, the spinning liquid advancement speed is 1ml / h, the temperature is 45℃, and the relative humidity is 40%; the number of jet needles of the electrospinning equipment is 1500, the speed of roller hot pressing molding is 5m / min, the temperature of roller hot pressing molding is 280℃, and the pressure of roller hot pressing molding is 10MPa.
[0051] Step 4: Place the composite material structure intermediate into a plasma treatment chamber, use oxygen as the treatment gas, set the power to 100W, maintain the gas pressure at a vacuum environment of 0.2Pa, the treatment time is 3 minutes, the treatment distance is controlled at 2cm, and the treatment temperature is maintained at room temperature.
[0052] Embodiment 2
[0053] Step 1: According to the mass percentage, 35 parts of polyarylate staple fibers and 65 parts of polyarylate pulp fibers are dissolved in 10,000 parts of water at a speed of 2,100 rpm for 10 minutes to form a slurry, and placed in a slurry tank with a stirring speed of 75 rpm, and then wet-coated through an inclined mesh paper base at a speed of 15 m / min. After the papermaking is formed, it is dried at 125°C to obtain a polyarylate base layer.
[0054] The length of the polyarylate staple fiber is 10 mm, the fineness of the polyarylate staple fiber is 1D, the length of the polyarylate pulp fiber is 1.5 mm, the beating degree is 27°SR, and the basis weight of the polyarylate base layer is 16 g / m 2 .
[0055] Step 2: Dissolve and disperse 30 parts of polyarylate powder, 50 parts of polyvinylidene fluoride, 20 parts of nano zirconium dioxide and 0.2 parts of nano cellulose in 900 parts of a mixed solvent by mass, stir at 80°C for 1 hour, take out and let stand and cool for 15 minutes, and then filter and defoam to obtain a spinning solution.
[0056] The mixed solvent includes 50 parts of lithium chloride and 850 parts of methyl pyrrolidone.
[0057] Step three: inject the spinning solution into the electrospinning equipment, lay a polyarylate base layer on the receiving device, perform electrospinning to form a composite material layer, and obtain a composite material structure intermediate. Then, place the composite material structure intermediate in an ultrasonic cleaning tank for cleaning for 3 minutes. The cleaning liquid is 55% ethanol solution. After cleaning, it is dried at 90°C and rolled and hot-pressed.
[0058] Among them, the amount of spinning solution is 2g / m 2 The pressure of the electrospinning equipment is 25kv, the distance between the jet needle and the receiving roller is 30cm, the spinning solution advancement speed is 1ml / h, the temperature is 45℃, and the relative humidity is 40%; the number of jet needles of the electrospinning equipment is 1500, the speed of roller hot pressing is 8m / min, the temperature of roller hot pressing is 280℃, and the pressure of roller hot pressing is 10MPa.
[0059] Step 4: Place the composite material structure intermediate into a plasma treatment chamber, use oxygen as the treatment gas, set the power to 100W, maintain the gas pressure at a vacuum environment of 0.2Pa, the treatment time is 3 minutes, the treatment distance is controlled at 2cm, and the treatment temperature is maintained at room temperature.
[0060] Embodiment 3
[0061] Step 1: According to the weight percentage, 55 parts of polyarylate staple fibers and 45 parts of polyarylate pulp fibers are dissolved in 10,000 parts of water at a speed of 2,500 rpm for 8 minutes to form a slurry, and placed in a slurry tank with a stirring speed of 150 rpm, and then wet-coated through an inclined mesh paper base at a speed of 19 m / min. After the papermaking is formed, it is dried at 125°C to obtain a polyarylate base layer.
[0062] The length of the polyarylate staple fiber is 8 mm, the fineness of the polyarylate staple fiber is 1D, the length of the polyarylate pulp fiber is 1.5 mm, the beating degree is 23°SR, and the basis weight of the polyarylate base layer is 25 g / m 2 .
[0063] Step 2: Dissolve and disperse 40 parts of polyarylate powder, 50 parts of polyvinylidene fluoride, 10 parts of nano zirconium dioxide and 0.08 parts of nano cellulose in 900 parts of a mixed solvent by mass, stir at 80°C for 1 hour, take out and let stand and cool for 15 minutes, and then filter and defoam to obtain a spinning solution.
[0064] The mixed solvent includes 100 parts of lithium chloride and 800 parts of dimethylacetamide.
[0065] Step three: inject the spinning solution into the electrospinning equipment, lay a polyarylate base layer on the receiving device, perform electrospinning to form a composite material layer, and obtain a composite material structure intermediate. Then, place the composite material structure intermediate in an ultrasonic cleaning tank for cleaning for 3 minutes. The cleaning liquid is 55% ethanol solution. After cleaning, it is dried at 90°C and rolled and hot-pressed.
[0066] Among them, the amount of spinning solution is 5g / m 2 The pressure of the electrospinning equipment is 25kv, the distance between the jet needle and the receiving roller is 30cm, the spinning solution advancement speed is 1ml / h, the temperature is 45℃, and the relative humidity is 40%; the number of jet needles of the electrospinning equipment is 1500, the speed of roller hot pressing is 8m / min, the temperature of roller hot pressing is 280℃, and the pressure of roller hot pressing is 10MPa.
[0067] Step 4: Place the composite material structure intermediate into a plasma treatment chamber, use oxygen as the treatment gas, set the power to 100W, maintain the gas pressure at a vacuum environment of 0.2Pa, the treatment time is 3 minutes, the treatment distance is controlled at 2cm, and the treatment temperature is maintained at room temperature.
[0068] Embodiment 4
[0069] Step 1: According to the mass percentage, 23 parts of polyarylate staple fibers and 77 parts of polyarylate pulp fibers are dissolved in 10,000 parts of water at a speed of 2,500 rpm for 8 minutes to form a slurry, and placed in a slurry tank with a stirring speed of 150 rpm, and then wet-coated through an inclined mesh paper base at a speed of 19 m / min. After the papermaking is formed, it is dried at 125°C to obtain a polyarylate base layer.
[0070] The length of the polyarylate staple fiber is 8 mm, the fineness of the polyarylate staple fiber is 1D, the length of the polyarylate pulp fiber is 1.5 mm, the beating degree is 23°SR, and the basis weight of the polyarylate base layer is 20 g / m 2 .
[0071] Step 2: Dissolve and disperse 30 parts of polyarylate powder, 60 parts of polyvinylidene fluoride, 10 parts of nano zirconium dioxide and 0.1 parts of nano cellulose in 900 parts of a mixed solvent by mass, stir at 80°C for 1 hour, take out and let stand to cool for 15 minutes, and then filter and defoam to obtain a spinning solution.
[0072] The mixed solvent includes 70 parts of lithium chloride and 830 parts of dimethylacetamide.
[0073] Step three: inject the spinning solution into the electrospinning equipment, lay a polyarylate base layer on the receiving device, perform electrospinning to form a composite material layer, and obtain a composite material structure intermediate. Then, place the composite material structure intermediate in an ultrasonic cleaning tank for cleaning for 3 minutes. The cleaning liquid is 55% ethanol solution. After cleaning, it is dried at 90°C and rolled and hot-pressed.
[0074] Among them, the amount of spinning solution is 5g / m 2 The pressure of the electrospinning equipment is 25kv, the distance between the jet needle and the receiving roller is 30cm, the spinning solution advancement speed is 1ml / h, the temperature is 45℃, and the relative humidity is 40%; the number of jet needles of the electrospinning equipment is 1500, the speed of roller hot pressing is 2m / min, the temperature of roller hot pressing is 280℃, and the pressure of roller hot pressing is 10MPa.
[0075] Step 4: Place the composite material structure intermediate into a plasma treatment chamber, use oxygen as the treatment gas, set the power to 100W, maintain the gas pressure at a vacuum environment of 0.2Pa, the treatment time is 3 minutes, the treatment distance is controlled at 2cm, and the treatment temperature is maintained at room temperature.
[0076] Embodiment 5
[0077] Step 1: According to the mass percentage, 45 parts of polyarylate staple fibers and 55 parts of polyarylate pulp fibers are dissolved in 10,000 parts of water at a speed of 2,500 rpm for 8 minutes to form a slurry, and placed in a slurry tank with a stirring speed of 150 rpm, and then wet-coated through an inclined mesh paper base at a speed of 19 m / min. After the papermaking is formed, it is dried at 125°C to obtain a polyarylate base layer.
[0078] The length of the polyarylate staple fiber is 8 mm, the fineness of the polyarylate staple fiber is 1D, the length of the polyarylate pulp fiber is 1.5 mm, the beating degree is 23°SR, and the basis weight of the polyarylate base layer is 10 g / m 2 .
[0079] Step 2: Dissolve and disperse 30 parts of polyarylate powder, 60 parts of polyvinylidene fluoride, 10 parts of nano zirconium dioxide and 0.2 parts of nano cellulose in 900 parts of a mixed solvent by mass, stir at 80°C for 1 hour, take out and let stand and cool for 15 minutes, and then filter and defoam to obtain a spinning solution.
[0080] The mixed solvent includes 60 parts of lithium chloride and 840 parts of dimethylacetamide.
[0081] Step three: inject the spinning solution into the electrospinning equipment, lay a polyarylate base layer on the receiving device, perform electrospinning to form a composite material layer, and obtain a composite material structure intermediate. Then, place the composite material structure intermediate in an ultrasonic cleaning tank for cleaning for 3 minutes. The cleaning liquid is 55% ethanol solution. After cleaning, it is dried at 90°C and rolled and hot-pressed.
[0082] Among them, the amount of spinning solution is 5g / m 2 The pressure of the electrospinning equipment is 25kv, the distance between the jet needle and the receiving roller is 30cm, the spinning solution advancement speed is 1ml / h, the temperature is 45℃, and the relative humidity is 40%; the number of jet needles of the electrospinning equipment is 1500, the speed of roller hot pressing is 4m / min, the temperature of roller hot pressing is 280℃, and the pressure of roller hot pressing is 10MPa.
[0083] Step 4: Place the composite material structure intermediate into a plasma treatment chamber, use oxygen as the treatment gas, set the power to 100W, maintain the gas pressure at a vacuum environment of 0.2Pa, the treatment time is 3 minutes, the treatment distance is controlled at 2cm, and the treatment temperature is maintained at room temperature.
[0084] Comparative Example 1
[0085] Step 1: According to the mass percentage, 100 parts of polypropylene fibers are dissolved in 10,000 parts of water at a speed of 3,000 rpm for 8 minutes to form a slurry, and placed in a slurry tank with a stirring speed of 50 rpm, and then wet-coated through an inclined mesh paper base at a running speed of 19 m / min. After the papermaking is formed, it is dried at 125°C to obtain a polypropylene base layer.
[0086] The length of the polypropylene fiber is 7 mm, and the basis weight of the polypropylene base layer is 30 g / m 2 .
[0087] Step 2: According to the mass fraction, 100 parts of polypropylene fibers are melt-extruded at 170°C to obtain a polypropylene melt; then, the polypropylene melt is subjected to electrostatic spinning to form a composite material layer to obtain a composite material structure intermediate, and then, the composite material structure intermediate is subjected to roller hot pressing molding.
[0088] Among them, the spinning amount is 10g / m 2 The pressure of the electrospinning equipment is 25kv, the distance between the jet needle and the receiving roller is 30cm, and the spinning liquid propulsion speed is 1ml / h; the number of jet needles of the electrospinning equipment is 1500, the temperature of roller hot pressing molding is 180℃, the speed of roller hot pressing molding is 5m / min, and the pressure of roller hot pressing molding is 10MPa.
[0089] Step 3: Place the composite material structure intermediate into a plasma treatment chamber, use oxygen as the treatment gas, set the power to 100W, maintain the gas pressure at 0.2Pa in a vacuum environment, the treatment time is 3 minutes, the treatment distance is controlled at 2cm, and the treatment temperature is maintained at room temperature.
[0090] Comparative Example 2
[0091] Step 1: According to the mass percentage, 35 parts of polyarylate staple fibers and 65 parts of polyarylate pulp fibers are dissolved in water at a speed of 2100 rpm for 10 min to form a slurry, and placed in a slurry tank with a stirring speed of 150 rpm, and then wet-coated through an inclined mesh paper base at a running speed of 15 m / min. After the papermaking is formed, it is dried at 125°C to obtain a polyarylate base layer.
[0092] The length of the polyarylate staple fiber is 10 mm, the fineness of the polyarylate staple fiber is 1D, the length of the polyarylate pulp fiber is 1.5 mm, the beating degree is 27°SR, and the basis weight of the polyarylate base layer is 16 g / m 2 .
[0093] Step 2: Dissolve and disperse 30 parts of polyarylate powder, 50 parts of polyvinylidene fluoride, 20 parts of nano zirconium dioxide and 0.2 parts of nano cellulose in 900 parts of a mixed solvent by mass, stir at 80°C for 1 hour, take out and let stand and cool for 15 minutes, and then filter and defoam to obtain a spinning solution.
[0094] The mixed solvent includes 50 parts of lithium chloride and 850 parts of methyl pyrrolidone.
[0095] Step three: inject the spinning solution into the electrospinning equipment, lay a polyarylate base layer on the receiving device, perform electrospinning to form a composite material layer, and obtain a composite material structure intermediate. Then, place the composite material structure intermediate in an ultrasonic cleaning tank for cleaning for 3 minutes. The cleaning liquid is 55% ethanol solution. After cleaning, it is dried at 90°C and rolled and hot-pressed.
[0096] Among them, the amount of spinning solution is 2g / m 2The pressure of the electrospinning equipment is 25kv, the distance between the jet needle and the receiving roller is 30cm, the spinning liquid advancement speed is 1ml / h, the temperature is 45℃, and the relative humidity is 40%; the number of jet needles of the electrospinning equipment is 1500, the speed of roller hot pressing is 8m / min, the temperature of roller hot pressing is 280℃, and the pressure of roller hot pressing is 10MPa.
[0097] Comparative Example 3
[0098] Step 1: According to the mass percentage, 55 parts of polyarylate staple fibers and 45 parts of polyarylate pulp fibers are dissolved in water at a speed of 2500 rpm for 8 minutes to form a slurry, and placed in a slurry tank with a stirring speed of 150 rpm, and then wet-coated through an inclined mesh paper base at a speed of 19 m / min. After the papermaking is formed, it is dried at 125°C to obtain a polyarylate base layer.
[0099] The length of the polyarylate staple fiber is 8 mm, the fineness of the polyarylate staple fiber is 1D, the length of the polyarylate pulp fiber is 1.5 mm, the beating degree is 23°SR, and the basis weight of the polyarylate base layer is 25 g / m 2 .
[0100] Step 2: Place the polyarylate substrate layer in an ultrasonic cleaning tank and clean it for 3 minutes. The cleaning solution is a 55% ethanol solution. After cleaning, it is dried at 90° C. and subjected to roller hot pressing molding.
[0101] The speed of the roller hot pressing molding is 8 m / min, the temperature of the roller hot pressing molding is 280° C., and the pressure of the roller hot pressing molding is 10 MPa.
[0102] Step 3: Place the hot-pressed polyarylate substrate layer into a plasma treatment chamber, use oxygen as the treatment gas, set the power to 100 W, maintain the gas pressure at 0.2 Pa in a vacuum environment, the treatment time is 3 minutes, the treatment distance is controlled at 2 cm, and the treatment temperature is maintained at room temperature.
[0103] The following are the standards for performance testing of the products prepared in Examples 1 to 5 and Comparative Examples 1 to 3 of the present application.
[0104] Porosity: GB / T 42697-2023; Tensile strength: GB / T12914-2018; Puncture strength: GB / T 10004—2008; Ionic conductivity: NB / T 10827-2021; Thermal decomposition temperature: GB / T37631-2019; Static contact angle: ASTMD724.
[0105] The following are the results of performance tests on the products prepared in Examples 1 to 5 and Comparative Examples 1 to 3 of the present application.
[0106] Table 1
[0107]
[0108] It can be seen from this that:
[0109] 1. Compared with Example 1, the material used for the base layer of Comparative Example 1 is polypropylene fiber, and the material used for electrospinning treatment is polypropylene powder. Therefore, the tensile strength, puncture strength and ion conductivity of Comparative Example 1 are all lower than those of Example 1, which shows that even if the structures are similar, the performance of the composite material structure prepared using polypropylene material is still lower than the performance of the composite material structure prepared using polyarylate material.
[0110] 2. Compared with Example 2, Comparative Example 2 was not subjected to hydrophilic treatment, and therefore, its static contact angle was much greater than that of Example 2, indicating that its adsorption and penetration performance to the electrolyte was far inferior to that of Example 2.
[0111] 3. Compared with Example 3, Comparative Example 3 was not subjected to electrospinning treatment. Therefore, its tensile strength and puncture strength were much smaller than those of Example 3, which shows that the dense hydrophilic composite material layer can effectively disperse stress and bear more load, thereby improving the deformation resistance of the composite material structure and making it less likely to be punctured during use.
[0112] 4. Compared with Examples 1 to 3, the basis weight of the base layer of Examples 4 to 5 is 10 g / m 2 ~20g / m 2 In the range of , it has both good mechanical strength and good ionic conductivity, which not only reduces the probability of low mechanical strength due to low quantity, but also reduces the probability of increased ion migration resistance due to high quantity.
[0113] 5. The thermal decomposition temperatures of the composite material structures prepared in Examples 1 to 5 are relatively high, indicating that the composite material structures prepared by the above method have good thermal stability.
[0114] The above is only a specific implementation of the present application. Obviously, various modifications and combinations can be made without departing from the spirit and scope of the present application. Accordingly, this specification and the drawings are only exemplary illustrations of the present application as defined by the attached claims, and are deemed to have covered any and all modifications, changes, combinations or equivalents within the scope of the present application. Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is intended to include these changes and variations. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be covered within the scope of protection of the present application. Therefore, the scope of protection of the present application shall be based on the scope of protection of the claims.
[0115] It should also be noted that in the device and method of the present application, each component or each step can be decomposed and / or recombined. Such decomposition and / or recombination should be regarded as equivalent solutions of the present application.
[0116] The above description of the disclosed aspects is provided to enable any person skilled in the art to make or use the present application. Various modifications to these aspects will be readily apparent to those skilled in the art, and the general principles defined herein may be applied to other aspects without departing from the scope of the present application. Therefore, the present application is not intended to be limited to the aspects shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
[0117] The above description has been given for the purpose of illustration and description. In addition, this description is not intended to limit the embodiments of the present application to the forms disclosed herein. Although multiple example aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, changes, additions and sub-combinations thereof.
Claims
1. A composite material structure, characterized in that: include: A hydrophilic polyarylate base layer and a hydrophilic composite material layer arranged on the hydrophilic polyarylate base layer, wherein the pore size of the hydrophilic composite material layer is smaller than the pore size of the hydrophilic polyarylate base layer.
2. The composite material structure according to claim 1, characterized in that: The porosity of the hydrophilic composite material layer is 0.25 to 1.2 times that of the hydrophilic polyarylate base layer, and the pore size of the hydrophilic composite material layer is 0.033 to 0.6 times that of the polyarylate base layer.
3. The composite material structure according to claim 1 or 2, characterized in that: The porosity of the hydrophilic polyarylate base layer is 50% to 80%, the pore size of the hydrophilic polyarylate base layer is 0.5 μm to 3 μm, the porosity of the hydrophilic composite material layer is 20% to 60%, and the pore size of the hydrophilic composite material layer is 0.1 μm to 0.3 μm.
4. The composite material structure according to claim 1 or 2, characterized in that: The material of the hydrophilic polyarylate base layer includes polyarylate staple fibers and polyarylate pulp fibers; the length of the polyarylate staple fibers is 5 mm to 20 mm, the fineness of the polyarylate staple fibers is 1.1D to 3.3D, and the length of the polyarylate pulp fibers is 1 mm to 2.5 mm.
5. The composite material structure according to claim 3, characterized in that: The basis weight of the hydrophilic polyarylate base layer is 2 g / m 2 ~40g / m 2 .
6. The composite material structure according to claim 1, characterized in that: The raw materials of the hydrophilic composite material layer include polyarylate powder and fluorine-containing resin; according to the mass fraction in the hydrophilic composite material layer, the polyarylate powder is 30 to 50 parts, and the fluorine-containing resin is 50 to 70 parts.
7. The composite material structure according to claim 6, characterized in that: The raw materials of the hydrophilic composite material layer also include nanocellulose, nano zirconium dioxide and a mixed solvent. According to the mass fraction in the hydrophilic composite material layer, the nanocellulose is 0.05 to 0.2 parts, the nano zirconium dioxide is 10 to 50 parts, and the mixed solvent is 480 to 3922 parts.
8. The composite material structure according to claim 7, characterized in that: The mixed solvent comprises a halide salt and a polar solvent that forms a cationic polar oxygen group complexed with the halide salt. Calculated by weight in the mixed solvent, the halide salt is 1 to 10 parts, and the polar solvent is 90 to 99 parts.
9. The composite material structure according to claim 8, characterized in that: The halide salt includes at least one of lithium chloride, potassium chloride, sodium chloride, lithium bromide and sodium bromide, and the polar solvent includes one or more of dimethylacetamide, methylpyrrolidone and dimethylformamide.
10. A method for preparing a composite material structure according to any one of claims 1 to 9, characterized in that: The preparation method comprises: Step 1: disintegrating polyarylate short fibers and polyarylate pulp fibers into slurry in water, and papermaking the slurry, and obtaining a polyarylate base layer after drying; Step 2: dissolving and dispersing polyarylate powder, fluorine-containing resin, nano zirconium dioxide and nano cellulose in a mixed solvent to obtain a spinning solution; Step 3: using the spinning solution to electrospin the polyarylate substrate layer to form a composite material layer, thereby obtaining a composite material structure intermediate; Step 4: Performing hydrophilic treatment on the composite material structure intermediate to obtain a composite material structure.
11. The method for preparing a composite material structure according to claim 10, characterized in that: In the step 1, the beating degree of the polyarylate staple fibers is 20°SR to 50°SR, and the speed of the debonding is 1000 rpm to 6000 rpm.
12. The method for preparing a composite material structure according to claim 10, characterized in that: In step 3, the amount of the spinning solution is 1 g / m 2 ~20g / m 2 .
13. The method for preparing a composite material structure according to claim 10, characterized in that: The step three also includes: cleaning and hot pressing the composite material structure intermediate; the temperature of the hot pressing treatment is 240°C to 320°C, the time of the hot pressing treatment is 0.5min to 5min, and the pressure of the hot pressing treatment is 5 to 10MPa.
14. The method for preparing a composite material structure according to claim 10, characterized in that: In the step 4, the vacuum degree of the hydrophilic treatment is 5Pa to 100Pa, the output power of the hydrophilic treatment is 100W to 500W, and the time of the hydrophilic treatment is 5min to 30min.
15. Use of a composite material structure according to any one of claims 1 to 9 and / or a composite material structure prepared by the preparation method of the composite material structure according to any one of claims 10 to 14 in a lithium battery.
16. The use according to claim 15, characterized in that The application is application in separator paper.